MULTIKULTURALISME PADA MASA UMMAYAH DALAM SEJARAH PERADABAN ISLAM - Busthomi, Yazidul; Rudy Catur Rohman Kusmayadi (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Multiculturalism in general is a concept of culture and variations in individual behavior caused by differences in race, religion and social structure, which is currently a hot issue and study material in the realm of social order. Islam has existed for centuries as the center of an advanced and diverse civilization. Along with the spread of Islam to various regions of the world, Islamic kingdoms grew and had prosperous centers of trade, science and culture. One of the main characteristics of Islamic civilization is the ethnic, cultural and religious diversity that exists within it. The structure of society in Damascus consists of four main components, namely: 1. The first social class, namely the Muslim-Arab nation occupies the highest class in social stratification in Damascus. 2. The second social class, namely the converts, people who have just converted to Islam. 3. The third social class, namely the non-Muslim group. 4. The fourth social class, namely the slaves who lived within the center of power of the Umayyad Daula in Damascus.